The relative importance of total factor productivity and factors of production in income per worker: Evidence from the Brazilian states - Lízia de Figueiredo; Luciano Nakabashi (EconomiA, 2016)
Income per worker gap in different regions of Brazil is stunning. To assess the relative importance of factor of production and total factor productivity (TFP) in those income per worker disparities, development accounting exercises were carried out for the 1970, 1980, 1990, 2000 and 2010 years. In 1970, both types of capital stocks and TPF gaps were associated with the Brazilian states lower relative income in comparison to S\~ao Paulo state. Over the decades up to the year 2000, the Brazilian states have experienced a relevant capital deepening process, which account for income per work catching-up. However, the TFP gaps in relation to the reference state remain almost stable and their reduction is fundamental to the maintenance of the Brazilians states income per worker catching-up process. The conclusions remain similar when the analysis is conducted by means of distinct proxies of physical capital. When considering the human capital qualitative aspect, we noticed a greater human capital gap among the Brazilian states in relation to S\~ao Paulo State and, as a consequence, a reduction in the TFP relative gap. – – O diferencial de renda por trabalhador em diferentes regi\~oes do Brasil é impressionante. Para avaliar a importância relativa dos fatores de produç\~ao e da produtividade total dos fatores (PTF) na disparidade de renda por trabalhado, exercícios de contabilidade do desenvolvimento foram realizados para 1970, 1980, 1990, 2000 e 2010. Em 1970, a renda por trabalhador dos estados brasileiros em relaç\~ao ao paulista era inferior devido às defasagens existentes em ambos os tipos de capital e da PTF. Ao longo das décadas até 2000, os estados brasileiros experimentaram um processo relevante de aprofundamento de capital físico, que acabou levando a um processo de “catching-up”. No entanto, as defasagens da PTF em relaç\~ao ao estado de referência permaneceram praticamente estáveis em todo o período, sendo que a sua reduç\~ao é fundamental para que os estados brasileiros mantenham o processo de “catching-up” da renda por trabalho. As conclus\~oes s\~ao semelhantes quando a análise é feita com distintas proxies de capital físico. Ao considerar o aspecto qualitativo do capital humano, notamos uma maior defasagem de capital humano dos estados brasileiros em relaç\~ao ao Estado de S\~ao Paulo e, como consequência, uma reduç\~ao nos diferenciais da PTF.
Keywords: O47; R11; 330; Development accounting; Economic growth; Total factor productivity; Brazilian states